2020
DOI: 10.1177/0898264320916959
|View full text |Cite
|
Sign up to set email alerts
|

Association of High-Density Lipoprotein Cholesterol With Cognitive Function: Findings From the PROspective Study of Pravastatin in the Elderly at Risk

Abstract: Objective: We aimed to examine whether variability in high-density lipoprotein cholesterol (HDL-c) over time was associated with cognitive function. Method: We conducted a post hoc analysis of the PROspective Study of Pravastatin in the Elderly at Risk (PROSPER) trial. Our sample included 4,428 participants with at least two repeated HDL-c measures between Months 3 and 24 postbaseline and with cognitive assessments at Month 30. HDL-c variability was defined as the intraindividual standard deviation over each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Previous studies clarify the associations of higher visit-tovisit cholesterol with cognitive decline (Smit et al, 2016;Grasset et al, 2020;Hua et al, 2020). In these studies, CV, VIM, and SD reflect the degree of intraindividual dispersion of cholesterol, including downward and upward fluctuations.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies clarify the associations of higher visit-tovisit cholesterol with cognitive decline (Smit et al, 2016;Grasset et al, 2020;Hua et al, 2020). In these studies, CV, VIM, and SD reflect the degree of intraindividual dispersion of cholesterol, including downward and upward fluctuations.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have been clari ed associations of higher visit-to-visit TC, NHDL-C and LDL-C with cognitive decline [10,12,20]. In these studies, CV, VIM and SD re ected the degree of dispersion of cholesterol including downward and upward uctuations.…”
Section: Discussionmentioning
confidence: 99%
“…These contaminants are toxic to human body and may lead to DNA damage and death of brain cells, resulting in neurobehavioral impairment and cognitive dysfunction [8]. Additionally, exposure to polluted drinking water has been found to be associated with a higher risk of having dysfunctional cholesterol status and developing dyslipidemia, which is associated with brain aging and perhaps cognitive dysfunction [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There is even less information on the relationship between drinking water quality and cognitive function for older adults in China and the population-based evidence is still unavailable. Although elevated LDL has been shown to be associated with cognitive decline [33,34], the relationship between dyslipidemia and cognitive function has been less explored and results have been inconsistent [5,14]. Some studies reported no association or an inverse association between TC and cognitive function in adults aged 65 and above [35,36], whereas others showed a positive association in midlife with a longer follow-up observational period [5,37].…”
Section: Introductionmentioning
confidence: 99%